Gestión de la comunicación institucional para la proyección de la imagen corporativa de la unidad educativa del milenio Ángel Polibio Chaves, cantón San Miguel, período octubre 2023 a febrero 2024 - Moreta Mazón, Julio Javier (2024)
This work is the result of the research carried out in the Angel Polibio Chaves Millennium Educational Unit of San Miguel de Bolívar with the objective of determining the projection of the corporate image, as a result of the institutional communication management of the Unit; For this purpose, we worked with a mixed approach in order to have clear and precise information on the communication management carried out by the Educational Unit, with the descriptive modality and the documentary and field type; The interview with the school authority, the survey of selected personnel and observation of the institution were applied as research instruments; which resulted in the lack of adequate institutional communication, which in one way or another affects the corporate image of the Educational Unit; Therefore, it is recommended to take into account the organization of a communication department, train staff, plan the work that must be carried out with regard to internal and external communication; in addition to optimizing administrative management, in order to significantly improve the projection of the corporate image of the campus; For this purpose, a proposal of strategies to be implemented to achieve the objectives established in this work is prepared.